PERLINDUNGAN HAK ASASI MANUSIA DALAM OPERASI PENINDAKAN YANG DILAKUKAN OLEH SATUAN BRIMOB PELOPOR - Rulis, Muhammad; Hartoyo, Hartoyo; N, Dedi Wardana (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This research is motivated by the urgency of protecting human rights (HR) in every law enforcement operation conducted by the Indonesian Police, particularly the Mobile Brigade (Brimob) Pelopor Unit. The research problems focus on how the legal procedures of enforcement operations are carried out and the potential human rights violations that may occur. This study employs a normative juridical method with a statutory approach, supported by empirical data from observations and interviews. The findings indicate that Brimob enforcement operations are regulated by several legal instruments, including Law No. 2 of 2002 on the Indonesian National Police, Police Regulation (Perkap) No. 1 of 2009 on the Use of Force, Perkap No. 8 of 2009 on the Implementation of Human Rights Principles, and Perkap No. 2 of 2019 on Riot Control. The implementation consists of three stages: planning, execution, and evaluation, with legality, necessity, and proportionality as guiding principles. However, the potential for human rights violations remains, particularly in cases of excessive use of force, restrictions on freedom of assembly, and weak accountability mechanisms. Therefore, strengthening human rights-based training, independent supervision, and strict internal accountability are essential to ensure that enforcement operations remain consistent with the rule of law and the protection of human rights